Análisis Numérico de un método Galerkin discontinuo aplicado a un problema unidimensional - Timoteo Sánchez, Martha Hilda (2025)
In this work, we apply the discontinuous Galerkin SIPG method proposed in [12] to a Diffusion-Absorption problem with Dirichlet-type boundary conditions. We numerically determine that there is an explicit dependence on the stabilization parameter with respect to the degree of the polynomial used by the method. We present the error in the energy norm and establish an estimate of the error in the L2 norm, using the Aubin-Nitsche trick.